2017
DOI: 10.1039/c6py01779g
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous SARA ATRP using inorganic sulfites

Abstract: Aqueous supplemental activator and reducing agent atom transfer radical polymerization (SARA ATRP) using inorganic sulfites was successfully carried out for the first time. Under optimized conditions, a well-controlled poly[oligo(ethylene oxide) methyl ether acrylate] (POEOA) was obtained with <30 ppm of soluble copper catalyst using tris(2-pyridylmethyl)amine (TPMA) ligand in the presence of an excess of halide salts (e.g. NaCl). Inorganic sulfites (e.g. Na2S2O4) were continuously fed into the reaction mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 64 publications
2
30
0
Order By: Relevance
“…The relevant reactions included in the model are based on previously reported experimental and simulation results. 14,21,2628,33,38,39 Reactions include: dissolution and dissociation of the inorganic sulfite (1, 2); supplemental activation of (macro)alkyl halides by SO 2 •− (3, 4); reduction of X–Cu II /L and Cu II /L complexes by SO 2 •− (5, 6), ATRP equilibrium between (macro)alkyl halides and (macro)radicals (7, 8); halidophilicity equilibrium of Cu I /L and Cu II /L complexes (9, 10); addition of alkyl halide-derived radicals (R • ) to the monomer (11); propagation (12); termination of two R • radicals (13); termination of R • with a polymer radical ( normalPnormaln) (14) and termination of two normalPnormaln radicals (15). Reaction rate coefficients were either quantified by isolating the respective reactions ( vide infra ) or based on results provided in previous literature reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant reactions included in the model are based on previously reported experimental and simulation results. 14,21,2628,33,38,39 Reactions include: dissolution and dissociation of the inorganic sulfite (1, 2); supplemental activation of (macro)alkyl halides by SO 2 •− (3, 4); reduction of X–Cu II /L and Cu II /L complexes by SO 2 •− (5, 6), ATRP equilibrium between (macro)alkyl halides and (macro)radicals (7, 8); halidophilicity equilibrium of Cu I /L and Cu II /L complexes (9, 10); addition of alkyl halide-derived radicals (R • ) to the monomer (11); propagation (12); termination of two R • radicals (13); termination of R • with a polymer radical ( normalPnormaln) (14) and termination of two normalPnormaln radicals (15). Reaction rate coefficients were either quantified by isolating the respective reactions ( vide infra ) or based on results provided in previous literature reports.…”
Section: Resultsmentioning
confidence: 99%
“…14,2633 This avoided the continuous generation of soluble Cu species introduced into the system by activation of alkyl halides by Cu 0 and by comproportionation, effectively retaining a reduced concentration of metal catalyst. 14 Control experiments revealed that Na 2 S 2 O 4 can indeed activate alkyl halides as well as reduce Cu II Br 2 /L deactivator complex, thus acting as a typical SARA agent, similar to Cu 0 14,33 . However, no detailed mechanistic investigations have been conducted to evaluate the relative contribution of the participating reactions during a SARA ATRP with inorganic sulfites.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium dithionite (Na 2 S 2 O 4 ) is a well‐known reducing agent, which has been previously used by our group as SARA agent for the SARA ATRP of different monomers in both organic and aqueous media near room temperature conditions . This inexpensive inorganic salt is also known for its ability to scavenge oxygen molecules .…”
Section: Resultsmentioning
confidence: 99%
“…By adhering to these “rules,” well‐controlled polymerizations of various water‐soluble monomers have been reported via normal ATRP, and different ATRP techniques based on the regeneration of the Cu(I) activator . Indeed, radical termination in ATRP causes the accumulation of [XCu II L] + deactivators, ultimately leading to early halt of the polymerization.…”
Section: Introductionmentioning
confidence: 99%